1997
DOI: 10.1007/bf01294729
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid levels of alpha-tocopherol (vitamin E) in Parkinson's disease

Abstract: We compared CSF and serum levels, and the CSF/serum ratio of alpha-tocopherol (vitamin E), measured by HPLC, in 34 patients with Parkinson's disease (PD) and 47 controls. CSF and serum vitamin E levels were correlate. The mean CSF and serum vitamin E levels, and the CSF/serum ratio of PD patients did not differ significantly between the groups. There was no influence of antiparkinsonian therapy on CSF vitamin E levels. CSF vitamin E levels did not correlate with age, age at onset, duration of the disease, scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…In the cerebrospinal fluid (CSF) from PD patients, some reports showed normal vitamin E [41] and glutathione [42] levels and increased 8-hydroxyguanosine (8-OHG) [43] and 8-hydroxy-2V -deoxygunanosine (8-OHdG)/8-OHG levels [44]. There is a potential relationship between plasma and CSF in levels of antioxidants and oxidation products.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the cerebrospinal fluid (CSF) from PD patients, some reports showed normal vitamin E [41] and glutathione [42] levels and increased 8-hydroxyguanosine (8-OHG) [43] and 8-hydroxy-2V -deoxygunanosine (8-OHdG)/8-OHG levels [44]. There is a potential relationship between plasma and CSF in levels of antioxidants and oxidation products.…”
Section: Discussionmentioning
confidence: 96%
“…There is a potential relationship between plasma and CSF in levels of antioxidants and oxidation products. In fact, Molina et al [41] reported that vitamin E levels in serum were correlated with those in CSF. The redox state of coenzyme Q10 in CSF would also bring valuable information on oxidative stress in the brain of PD patients.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously argued that α -tocopherol and γ -tocopherol are correlated in healthy subjects so that epidemiological studies associating dietary vitamin E or plasma vitamin E with health benefits may have indexed an unanticipated auto-correlation between the two tocopherol variants [63]. PD brain, plasma and CNS are not depleted in α -tocopherol [42,104] but γ -tocopherol has not been investigated. In light of recent findings described above that γ -tocopherol uniquely protects against an animal model of PD, more epidemiological studies are justified to explore non- α -tocopherol correlations with PD risk.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…There are no differences in the amount of vitamin E in the cerebellum (Dexter et al, 1992) or CSF (Molina et al, 1997) between PD patients and healthy individuals. Clinical trials also show no neuroprotective benefit of taking vitamin E (Fernandez-Calle et al, 1992; LeWitt, 1994; Morens et al, 1996).…”
Section: Vitamin D Beta-carotene and Riboflavin Are Candidates For Nmentioning
confidence: 99%